IDENTIFIKASI BIODIVERSITAS TUMBUHAN DI DESA SAWAHAN, NGEMPLAK, BOYOLALI - Frista Ananda Rizky; Hasna Khairunnisa (Yayasan Nusantara Hasana Berdikari, 2023)
Sawahan Village is one of the villages in Central Java that is included in the Urban Fringe area. Its location in the Urban Fringe area causes high land conversion activities in the village. Land function change activities have a direct impact on the smaller site of Green Open Space which then affects reducing tree biodiversity in Sawahan Village. Therefore, this study was conducted to achieve an inventory of the species in Sawahan Village and to determine the diversity and composition of invasive alien plants in the vegetation community in Sawahan Village. The research combines qualitative and quantitative description methods with data collection techniques through field surveys using sample plots. The entire sample plots used were 38 plots with a size of 20x20m, carried out in 15 blocks in Sawahan Village. The results showed that the tree species found in Sawahan Village were 47, with a total of 1,724 individuals. Arecaceae and Myrtaceae is the most dominant family in Sawahan Village with each family has a total of as many species as five Species. At the species level, Musa acuminata Colla, which belongs to the Musaceae family, is the plant species with the highest Important Value Index (IVI), with a value of 31.39%.